The milk production of reindeer cows and the share of milk in the growth of reindeer calves - Varo, Mikko; Varo, Hannu (Agricultural and Food Science, 1971)
The milk quantities obtained from the reindeer cows in the present study are probably, due to technical difficulties in the milking, lower than the actual values. For this reason the figures on the milk producing ability, and the connection between the milk yield and other characteristics of the cow or its calf, are bound to be uncertain. The general composition of reindeer milk is in fair agreement with results reported by other researchers (Tables 1, 4 and 5). Individual differences in the milk producing ability could clearly be detected. The correlations between the milk quantity and the constituents were usually not significant. The association between the dam’s spring weight and the protein percentage was significant (r = —0.47**). The range of the calves’ weights at birth was to a large degree mainteined during the entire period of growth (Table 9). The weight and growth of the calves was clearly dependent on the weight or on the size of the dam. The results obtained did not indicate any connection between the milk production characteristics of the dams and the growth of the calves (Tables 11 and 12). The spring weight of the dam has a more decisive influence on the growth of the calf than the birth weight of the latter. The results obtained seem to indicate that in the breeding for growth capacity, selection on the basis of the weight or size of the dams os of conclusive importance. In spite of the individual variations existing in the milk producing ability of reindeer cows, the importance ofthe quantity and composition of the milk seems to be covered by the genetically determined growth factors. As the size of reindeer can be determined more easily than the weight, the combined measure, (body length + chest girth), seems tobe a more suitable basis for evaluation.